The Influence Of Work Environment And Compensation On Employee Performance At CV Andika Tani Makmur In Blitar - Gita Wahyu Romadhon Putra; Rifki Hanif (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study analyzes the influence of the work environment and compensation system on employee work performance at CV Andika Tani Makmur, a company engaged in hybrid corn seed cultivation that relies on accuracy and manual labor. This topic is relevant because the consistency of employee performance directly shapes the quality of hybrid corn yields. As such, companies need empirical insight into which factors can effectively improve employee performance. Background Problems: This study is driven by the instability of employee performance in the maize cultivation process, especially regarding detasseling, crop cleanliness, and punctuality. This variation in performance raises a key question: can the work environment and compensation explain the difference in performance in CV Andika Tani Makmur? Novelty: This research focuses on the agricultural context in particular the corn seeding industry, which demands a high level of precision and consistency in the work. Although the work environment and compensation factors have been widely studied, few studies have examined these two variables simultaneously in the agribusiness sector, which has different fieldwork characteristics from other industrial sectors. Research Methods: The 62 participants in this associative quantitative study were selected using a saturation sampling method. The data were analyzed using multiple linear regression using a Likert-scale questionnaire. In order to quantify the impact of the work environment and compensation on employee performance, the study was conducted using tests for validity, reliability, classical assumptions, t-tests, F-tests, and R². Finding/Results: According to the results, there is a favorable and substantial relationship between employee performance and the work environment and compensation. When compared to other workplace factors, compensation has a statistically significant impact on Employee Performance. Conclusion: Improving the work environment and implementing performance-based compensation is an effective strategy to increase productivity and maintain production quality. These findings have practical implications for agricultural companies in designing more responsive and evidence-based human resource management policies.